Breastfeeding and infection control measures among lactating COVID-positive mothers: A retrospective study - Barathy Chandrasegaran; Jayavani Ramasundaram Loganathan; Devi Kitty; Thiagarajan Srinivasan; Jayapriya Mounissamy; Jennifer Francis Xavier (Asian Journal of Medical Sciences, 2022)
Background: Exclusive breastfeeding along with infection prevention measures is recommended for lactating COVID-positive mothers as benefits outweigh the risk. Aims and Objectives: The present study was undertaken to assess the feeding and infection prevention measures among the COVID-19 infected lactating mothers in Indira Gandhi Medical College and Research Institute, Puducherry to identify areas of concern. Materials and Methods: The cross-sectional and observational study was conducted by telephonic survey after verbal consent on a series of 103 COVID-positive postnatal mothers regarding their feeding practices and infection prevention measures. Descriptive statistics was used. Results: Breastfeeding was given by 72 (69.9%), mixed feeding by 27 mothers (26.2%), and formula feeds by four (3.9%). Overall, exclusive breastfeeding was given by 66 mothers (64.1%). With respect to infection prevention measures, high performance of frequent/always was observed for use of hand hygiene (n=90, 87.3%) and use of mask (n=81, 78.5%). Conclusion: Despite the pandemic situation, the most COVID-positive mothers breastfed their infants with fair compliance to infection prevention measures.